O serviço militar compulsório para médicos: uma abordagem da teoria dos deveres fundamentais à luz da ética da alteridade - Vieira, Pedro Gallo (2012)
The research in the line of Democracy, Fundamental Rights and Citizenship addresses, using the dialectical methodology, layoffs judicial incorporation of doctors to compulsory military service in peacetimes face fundamental duties. Judicial decisions understand that doctors have dispensed at 18 years got rid of military duty. These dispensations reach effective military court, tending to derail various activities of the Armed Forces, especially the Civic and Social Actions. First, the rising role of constitutional fundamental duties in literature today, when will perform duties as a fake invitation to dictatorships. Furthermore it is observed that an excess of rights without proper liability tends impair own right. Pointing to solidarity, brotherhood and citizenship as a source of fundamental duties and foundation in the dignity of the other figure. Martin Buber and his dialectic of I/thou point that the being is not being if don’t have to be another being, and so the rights will be attached to the duties and vice versa, an ethics of alterity and the idea of fraternity, solidarity and citizenship Then the doctor military enlistment is exposed by the issue of the Armed Forces in Brazilian history. These are the reasons raised the constituent power to opt for compulsory military service and the framework of the physician in this context. The professional ethos is comparing military activities. In the last stage of objectives, is verified military service to physicians as a way of safeguarding the fundamental rights and their limits. The military medical service is in fact a fundamental duty when linked to the promotion of fundamental rights related to the Armed Forces. In situations of national defense or security of health care in extraordinary situations when the civilian doctors are not qualified to act. This duty will be imposed on all physicians regardless of whether or not funded his studies and his military subordination should primarily serve the professional code of ethics, then return to the military command.